The First Scientific Correspondents: on the Problem of Collecting Folklore Material in Yakutia in 1930−40th of the XX Century - Danilova, Anna; Larionova, Anna; Orosina, Nadezhda; Charina, Olga (International Journal of Psychosocial Rehabilitation, 2020)
This article is dedicated to the problem of studying the gathering activities of the first scientific correspondents of Yakutia, as well as the principles of recording folklore materials in text and musical notation. The first part analyzes handwritten scripts of the Yakut epos called “olonkho” of the correspondents of the Vilyuysky folklore and ethnographic expedition of 1938, held by the Institute of Languages and Cultures at the Council of People’s Commissars of the Yakut ASSR. As a result of the expedition, A. A. Savvin and his correspondents recorded six texts; three notes were recorded by A. Savvin, and two notes by his correspondents. The study of the textual features of manuscripts revealing basic principles and methods of collecting epical texts has started. The second part of the article studies some characteristics of the correspondent’s work of the Institute of Languages and Cultures at the Council of People’s Commissars of the Yakut ASSR on the collection of Russian folklore in the downstream of the Indigirka River in 1946. It clarifies the character of the folklore of Russian oldtimers of the Russkoye Ustye. It also specifies the composition of the main fairy stories. The third part of the article describes the work method of the first Yakut composer M.N. Zhirkov with the choristers of the Yakut State Choir established by him at the Yakut State National Theater, which became his correspondents in gathering Yakut folk songs. Besides the choristers, his correspondents were local activists: local historians and teachers interested in folk songs. Thanks to their activities they made a collection of folk music at local level, as well as at folk concerts and Academic Olympics attended by performers of Yakut folk songs.